El procedimiento electrónico administrativo a la luz de las vicisitudes de la ley 1437 de 2011 (2016)
This work approaches the impact of the technologies of the information in the field of the Colombian administrative law; especially of the effects and more notable challenges of the implementation of his application according to the Law 1437 of 2011, Code of Administrative Procedure and of the Administrative Contentious thing. This under the suppositions of the administrative current named electronic government, habida under the ideology of the company of the information. First, a reconstruction is effected supposed fácticos and legal, for then, to integrate the normatividad that has governed the matter in last two decades, to conclude with an analysis of the efficiency of this type of procedure.